When does forecasting GAAP earnings entail unreasonable effort? - Laurion, Henry; Sloan, Richard (Journal of Accounting and Economics, 2022)
SEC rules require managers to reconcile their non-GAAP earnings forecasts with the most directly comparable GAAP forecasts unless doing so would entail ‘unreasonable effort.’ A significant number of managers rely on the unreasonable efforts exception to justify the omission of comparable GAAP forecasts. We analyze firms that rely on the unreasonable efforts exception and find that their non-GAAP earnings forecasts are more likely to exclude significant recurring expenses that are not excluded by analysts. Our results suggest that almost a third of managers exploit the unreasonable efforts exception to exclude significant recurring expenses from their earnings guidance.